PERANCANGAN JARINGAN BACKBONE MENGGUNAKAN ROUTING PROTOCOL EIGRP DI FAKULTAS TEKNIK UNIVERSITAS UDAYANA KAMPUS JIMBARAN - Muhajir Abidin, Naufal; Wiharta, D.M.; Sastra, N.P. (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
The backbone network infrastructure plan is one part of the development of information technology in the area of the Faculty of Engineering, Udayana University. Protocol Routing can be used to support data transmission, information, communication, etc. in the teaching and learning process. In practice, this region still uses the static routing method. But the increasing use of networks is designed by the New Network. The results of this design will be simulated with Cisco Packet Tracer 7.1.1. This new network uses the EIGRP routing protocol and will display some data, namely Packet loss, Throughput, Delay, and Fault Tolerant. Based on the results of testing and analysis of packet loss, in the 21 scenarios tested the same value is 0%. From this experiment the average throughput value was obtained 28.460 bps. This experiment the average value of Delay obtained is 10,95ms. Of the three trials, the data obtained included a very good category and entered at index 4 in the TIPHON qualification. In the Fault Tolerant test it is known that EIGRP has the ability to anticipate failures that occur on the network by finding alternative routes when the shortest path is not possible to pass.